Simulação da dinâmica operacional de uma linha industrial de abate de suínos - Fernandes, Carlos Aparecido (2005)
This work was carried out with the objective to implement a computational model for simulating the dynamics of an industrial slaughtering swine line. Modeled real system belongs the FRIMESA enterprise, located in Medianeira city, Paraná State, Brazil. Implemented model was classified as: dynamic, discrete and stochastic, and simulates thirty-four unity operations. For model implementation it was employed the simulation language EXTENDTM. Model validation was carried out comparing date related to five operational shifts, when it was slaughtered 1,346, 1,630, 1,360, 1,585 and 1,550 hogs. As contrasting parameters between data gotten from real system and generated by model, it was selected the following variables: (i) spent operational time; (ii) spent time from stunning area to scrap machine, (iii) spent time from stunning area to cold storage chamber; (iv) number of re-inspected carcasses; and (v) final number of edible slaughtered swine. At model validation was evidenced that for spent operational time averages, according to Tukey s test, at the significance level of 1%, it was not detected statistical differences between real system and generated simulation model data. Thus two sensitivity analyses were carried out. In the first it was modified the number of swine to be slaughtered from 1,000 to 2,000. It was observed that spent operational time decreases from 10.10 to 6.20 h. At the second, it was simulated the slaughtering of 1,346 head of hogs, and was varied processing rates from 300 to 600 heads per hour, at this situation operational times decreased from 8.10 to 7.40 h, respectively.